Metal–Carbon Hybrid Electrocatalysts Derived from Ion‐Exchange Resin Containing Heavy Metals for Efficient Hydrogen Evolution Reaction. Issue 20 (7th April 2016) - Zhou, Yucheng; Zhou, Weijia; Hou, Dongman; Li, Guoqiang; Wan, Jinquan; Feng, Chunhua; Tang, Zhenghua; Chen, Shaowei
Abstract : Transition metal–carbon hybrids have been proposed as efficient electrocatalysts for hydrogen evolution reaction (HER) in acidic media. Herein, effective HER electrocatalysts based on metal–carbon composites are prepared by controlled pyrolysis of resin containing a variety of heavy metals. For the first time, Cr2 O3 nanoparticles of 3–6 nm in diameter homogeneously dispersed in the resulting porous carbon framework (Cr–C hybrid) is synthesized as efficient HER electrocatalyst. Electrochemical measurements show that Cr–C hybrids display a high HER activity with an onset potential of −49 mV (vs reversible hydrogen electrode), a Tafel slope of 90 mV dec −1, a large catalytic current density of 10 mA cm −2 at −123 mV, and the prominent electrochemical durability. X‐ray photoelectron spectroscopic measurements confirm that electron transfer occurs from Cr2 O3 into carbon, which is consistent with the reported metal@carbon systems. The obtained correlation between metals and HER activities may be exploited as a rational guideline in the design and engineering of HER electrocatalysts. Abstract : A universal method is exploited for the integration of various heavy metal ions into carbon matrices for effective electrocatalysis. Among them, the Cr2 O3 ‐carbon exhibited a small onset potential of −49 mV (vs RHE) and a large catalytic current density of 10 mA cm −2 at −123 mV.